EVALUATED MAPPING OF NOISE POLLUTION OF URBANIZED TERRITORY - Mikhno, O.; Dobrovolsky, V.; Mykolaenko, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
Due to the acceleration of scientific and technological progress in the word, the level of traffic flows, industrialization, the number of automotive and technical equipment of the urban economy has increased, as a result of which people are constantly exposed to high-intensity noise. However, few people know that, by its effect on the human body, noise is more harmful than chemical pollution. Constant exposure to noise not only reduces hearing, but also causes other harmful effects – ringing in the ears, dizziness, headache, increased fatigue. People working in noisy conditions have an increased level of neuropsychiatric disorders.The article discusses the algorithm for evaluative mapping of noise pollution in the settlement area, which will ensure bringing the city territory to sanitary standards. The resulting noise map, which should be part of the master plan, captures the current and future state of the noise regime in the city. Accurate noise maps require the analysis of large number of different noise sources and, as a result, are very costly, although in most cases only an estimate of the noise loading is required. Therefore, it is advisable to build a hierarchy of noise sources and take into account the most significant. Such the most significant source of noise in settlements, as a rule, is a road network - streets and lanes on which movement of auto transport is allowed. The procedure for creating a geospatial model of noise pollution in the environment of a geographic information system described in the article includes creating a multibuffer for each noise source, translating the resulting vector image into a raster surface, superposition of individual object noise rasters, and creating an integrated evaluated map. Formed ways to improve the noise situation based on the results.
Keywords: noise pollution, urban area, noise map, urban environment, geospatial modeling